2015
DOI: 10.1016/j.procs.2015.05.417
|View full text |Cite
|
Sign up to set email alerts
|

Towards an Optimal Gradient-dependent Energy Functional of the PZ-SIC Form

Abstract: Results of Perdew-Zunger self-interaction corrected (PZ-SIC) density functional theory calculations of the atomization energy of 35 molecules are compared to those of high-level quantum chemistry calculations. While the PBE functional, which is commonly used in calculations of condensed matter, is known to predict on average too high atomization energy (overbinding of the molecules), the application of PZ-SIC gives a large overcorrection and leads to significant underestimation of the atomization energy. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…The exchange and correlation term of the PW91 functional is, however, not optimal for PZ-SIC. A smaller exchange enhancement factor can be used [27], bringing the exchange estimate closer to LDA, as illustrated by the fact that PZ-SIC gives an overcorrection when applied to PBE while it is an undercorrection when applied to LDA [24]. By developing an optimal exchange enhancement factor tailored to PZ-SIC, the scaling factor of 1/2 used here as well as in previous calculations based on the PBE functional [24,26] could be dropped.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exchange and correlation term of the PW91 functional is, however, not optimal for PZ-SIC. A smaller exchange enhancement factor can be used [27], bringing the exchange estimate closer to LDA, as illustrated by the fact that PZ-SIC gives an overcorrection when applied to PBE while it is an undercorrection when applied to LDA [24]. By developing an optimal exchange enhancement factor tailored to PZ-SIC, the scaling factor of 1/2 used here as well as in previous calculations based on the PBE functional [24,26] could be dropped.…”
Section: Discussionmentioning
confidence: 99%
“…While the correction is too small when applied to LDA, it is too large when applied to the PBE [7] and PW91 [25] functionals, as judged from atomization energy of molecules and band gaps [24,26]. Ideally, a new exchange enhancement factor in the generalized gradient functional form should be developed for use with PS-SIC, that has a weaker enhancement factor than PBE or PW91 [27]. Here, a scaling with a factor of 1/2 will be used as has been justified based on the adiabatic connection formula and has been shown to work well for a wide range of properties and various different types of systems [24,26] ( )…”
Section: Self-interaction Correctionmentioning
confidence: 99%
“…Core electrons are represented using Vanderbilt's ultrasoft pseudopoentials 29 . Due to a technical feature of the code it is convenient to compute the phonon modes in the LDA approximation using a Perdew-Zunger (PZ) functional 30 and norm-conserving pseudopotentials 29 33 with a spread value of 0.008 Ryd has been applied. The "Davidson" diagonalisation method with a mixing factor of 0.2 has been chosen for self consistency 34 .…”
Section: Computational Detailsmentioning
confidence: 99%
“…These found that while PZSIC improves properties like the dissociation pathway of heteroatomic molecules, it worsens the good description of semi-local functionals for nearequilibrium properties such as atomization energies, due to overcorrection 44,73 . This has come to be known as the paradox of SIC 74 .…”
Section: Introductionmentioning
confidence: 99%